SARS-CoV-2 Oral Vaccine Design Based on Nanoparticle Encapsulation with a Combination of Chitosan and Alginate - Cista Dewi, Ni Putu Fiona; Amelia Putri, Ni Luh Dian Saptari; Sudarma, I Wayan Ari; Sang Ayu Putu Chika Iswari Anjani; Saputra, Gusti Nyoman Oka; Yowani, Sagung Chandra (Journal of Food and Pharmaceutical Sciences, 2024)
Vaccination is the most effective intervention in reducing mortality rates due to COVID-19. Oral vaccines provide a more convenient process with a dual immune response (systemic and mucosal). Encapsulation is a strategic method that can be used to enhance the efficiency of oral vaccines. The combination of chitosan and alginate can protect the drug from gastrointestinal disturbances. Our research aims to nanoencapsulate the intravenous vaccine "Inavac" using chitosan and alginate polymers into a vaccine that can be consumed orally. The optimal formulation obtained is a formula with 1.75% chitosan; 0.1% NaTPP; and 0.05% alginate, with a stirring speed of 1150 rpm and a duration of 60 minutes. Characterization results show that the nanoencapsulated COVID-19 vaccine formula is nanometer-sized with homogeneous distribution and system stability correlated with good mucoadhesive power. Good design stability is indicated by the absence of significant changes in the formula levels (p-value = 0.69), appropriate functional groups, spherical surface morphology, and the highest vaccine release in the intestine (Simulated Intestine Fluid media). Optimum Formula Oral SARS-CoV-2 vaccine with chitosan and alginate polymers has great potential to be developed so that it can be an alternative choice for the community.